GE_GERICHTE P/14456/2012 vom 11. Februar 2013 - GE Cour de justice (2013)
; ADOLESCENT ; CURATEUR ; QUALITÉ POUR RECOURIR ; SUPPORT DE DONNÉES SONORES ET VISUELLES ; COMMUNICATION ; AVOCAT | CPP.107; CPP.108; CPP.102; CPP.428:CC; CP.292